(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
Beal’s Conjecture : The equation za = xb+yc has no solution in relatively prime positive integers x; y; z with a, b and c odd primes at least 3. A proof of this longstanding conjecture is given.